Mathematical Problem Solving Ability of Junior High School Students on Straight Line Equations - Dhita Rosalina Putri; Nita Hidayati (Unnes Journal of Mathematics Education Research, 2022)
The purpose of this study was to describe students' mathematical problem solving abilities in the material of straight line equations. This research was conducted using a qualitative approach with descriptive method to 34 students of class IX-H at one of the junior high schools in Karawang. This study used descriptive tests and debriefing for data collection. The description test used contains 4 questions regarding the ability to solve mathematical problems in the material of straight line equations. After conducting the research, it was concluded that the students' mathematical problem solving abilities, especially in the material of straight line equations, were classified as low, because there were 27 students who had poor problem solving skills. This is because the students are unable to determine the sufficiency of the data in the image, convert existing data into a mathematical model and solve it, explain and interpret the results according to the initial problems and choose and apply strategies to solve problems.